Digital Dialogues and Community 2.0 : After Avatars, Trolls and Puppets. - Brabazon, Tara (Chandos social media series., 2012)
Digital Dialogue and Community 2.0: After avatars, trolls and puppets explores the communities that use digital platforms, portals, and applications from daily life to build relationships beyond geographical locality and family links. The book provides detailed analyses of how technology realigns the boundaries between connection, consciousness and community. This book reveals that alongside every engaged, nurturing and supportive group are those who are excluded, marginalised, ridiculed, or forgotten. It explores the argument that community is not an inevitable result of communication. Follow.